PENGARUH DIVERSIFIKASI PERUSAHAAN DAN PRAKTIK MANAJEMEN LABA TERHADAP STRUKTUR MODAL (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia periode 2011-2015) - Zahrah, Fatimah; Muid, Dul (Diponegoro Journal of Accounting, 2017)
Capital structure is balancing or comparison between external capital (long-term) capital with internal capital. This research aims to gives insight into the relationship between corporate diversification and earning management practices to capital structure in manufacturing company listed on Indonesia Stock Exchange (IDX). The variables researched among others international market diversification, product diversification, asset-based Management, project-based earning management, and earning smoothing.The sampling method used in this research is purposive sampling method. The selected sample in this research as much as 41 manufacturing company. This research splits sample into two sub sample, ie multinational company- diversification (MND) and domestic company- diversification (DCD). The analysis used multiple regression analysis is preceded by The classical assumption test.The results of the data analysis indicate that the international market diversification, product diversification, asset-based earning management, project-based earning management, and income smoothing has a significant effect on capital structure towards MND or DCD.